2004
DOI: 10.3138/b123-8124-4390-5792
|View full text |Cite
|
Sign up to set email alerts
|

The Map as Intent: Variations on the Theme of John Snow

Abstract: Abstract"Critical geographers" concerned with cartography insist maps are first and foremost social artefacts that must be "read" as authorial documents rather than perceived as data statements. Their argument is typically dismissed as trivial because the relation between intent and output has rarely been demonstrated in a critical way. This article seeks to demonstrate the degree to which authorial intent defines map content and appearance through an analysis of a single set of maps. All are based on the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 14 publications
0
21
0
2
Order By: Relevance
“…It has been shown that maps play a key role in shaping people's beliefs about their environment and the world around them. In many cases, particularly outside of academia, maps are created and presented with the intention of promoting or reinforcing a particular belief (Koch 2004). A classic example of this is the standard highway map that proliferates in glove compartments around the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been shown that maps play a key role in shaping people's beliefs about their environment and the world around them. In many cases, particularly outside of academia, maps are created and presented with the intention of promoting or reinforcing a particular belief (Koch 2004). A classic example of this is the standard highway map that proliferates in glove compartments around the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…be viewed as a product of authorial intent rather than objective data presentation (Harley, 1989;Koch, 2004). This is somewhat tangential, but it is another illustration of the power of metaphor in how we conceive of and represent data and their relation to broader conceptions of reality.…”
Section: Association Of Research Libraries' Agenda For Developing E-smentioning
confidence: 99%
“…The subsequent section interrogates the consequences of these engagements and problematizes traditional understandings of authorship and authority, echoing recent debates on intentionality (Koch 2004). More specifically, it argues that what Jeremy Crampton and John Krygier (2006) call ''democratization of mapping'' (referring to Google Earth, for example) can be read as the culmination of a longer history of co-authorships between mapmakers and map users.…”
Section: Résumémentioning
confidence: 95%